EpiNet as a way of involving more physicians and patients in epilepsy research: Validation study and accreditation process. Issue 1 (3rd January 2017) - Bergin, Peter S.; Beghi, Ettore; Sadleir, Lynette G.; Brockington, Alice; Tripathi, Manjari; Richardson, Mark P.; Bianchi, Elisa; Srivastava, Kavita; Jayabal, Jayaganth; Legros, Benjamin; Ossemann, Michel; McGrath, Nicole; et al.
Summary: Objective: EpiNet was established to encourage epilepsy research. EpiNet is used for multicenter cohort studies and investigator‐led trials. Physicians must be accredited to recruit patients into trials. Here, we describe the accreditation process for the EpiNet‐First trials. Methods: Physicians with an interest in epilepsy were invited to assess 30 case scenarios to determine the following: whether patients have epilepsy; the nature of the seizures (generalized, focal); and the etiology. Information was presented in two steps for 23 cases. The EpiNet steering committee determined that 21 cases had epilepsy. The steering committee determined by consensus which responses were acceptable for each case. We chose a subset of 18 cases to accredit investigators for the EpiNet‐First trials. We initially focused on 12 cases; to be accredited, investigators could not diagnose epilepsy in any case that the steering committee determined did not have epilepsy. If investigators were not accredited after assessing 12 cases, 6 further cases were considered. When assessing the 18 cases, investigators could be accredited if they diagnosed one of six nonepilepsy patients as having possible epilepsy but could make no other false‐positive errors and could make only one error regarding seizure classification. Results: Between December 2013 and December 2014, 189 physicians assessed the 30 cases. Agreement with the steering committee regarding the diagnosis at step 1 ranged from 47% to 100%, and improved when information regarding tests was provided at step 2. One hundred five of the 189 physicians (55%) were accredited for the EpiNet‐First trials. The kappa value for diagnosis of epilepsy across all 30 cases for accredited physicians was 0.70. Significance: We have established criteria for accrediting physicians using EpiNet. New investigators can be accredited by assessing 18 case scenarios. We encourage physicians with an interest in epilepsy to become EpiNet‐accredited and to participate in these investigator‐led clinical trials.